A Dictionary of Sociology. - Scott, John, 1949- (Oxford, United Kingdom : Oxford University Press, 2014)
This dictionary of sociology provides over 2500 entries. It includes coverage of the major concepts from related disciplines and international coverage of terms, methods, and concepts, as well as biographical entries on major figures.
Formerly CIP.
Previous edition: 2009.
Keywords: Sociology -- Dictionaries